Hubungan Harga Diri dengan Pemahaman Membaca Pada Siswa Sekolah Dasar di Kota Bukittinggi - Zahra Farhanah; Duryati Duryati (Journal on Education, 2023)
This study aims to examine the relationship between self-esteem and reading comprehension among elementary school students in the city of Bukittinggi. Respondents in this study were 54 elementary school students in the city of Bukittinggi. Data collection uses a scale of self-esteem and reading comprehension with a Likert scale model. Categorization of data is grouped into three levels of categories namely high, medium and low. The biggest category of self-esteem variable is in the high category, namely 96.3% and the available reading category comprehension variable is also in the high category, namely 98.1%. The data analysis technique used in this study is the product moment statistical analysis technique. The results showed that there was a relationship between self-esteem and reading comprehension in elementary school students in the city of Bukittinggi with a significance value of 0.010 (p<0.05).